The Effect of Counseling on Premenstrual Syndrome Related Symptoms - Z Taghizadeh; M Shirmohammadi; M Mirmohammadali; M Arbabi; H Haghani (Tehran University of Medical Sciences, 2009)
Normal 0 false false false MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0pt 5.4pt 0pt 5.4pt; mso-para-margin:0pt; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} Background & Aim: Premenstrual syndrome (PMS) is a common psychosomatic disorder that affects 30-50% of women in reproductive ages. The purpose of this study was to determine the effect of a counseling program on premenstrual syndrome related symptoms."n"n Methods & Materials: This study was a randomized clinical trial in which the effect of a 3-sessioned counseling program on the PMS symptoms were assessed in 123 adolescent with PMS. The program included information providing, life style alteration, and providing stress management skills on symptoms of PMS. The participants were randomly allocated to intervention (n=67) and control (n=61) groups. Participants completed the demographic questionnaire, the PMS symptoms' daily record scale, and the symptom checklist 90-revised (SCL-90-R). Data were analyzed using the SPSS-11.5."n"n Results: The comparison of baseline data showed no significant difference between two groups regarding demographic characteristic and the PMS related symptoms. There were significant differences in the mean of total PMS severity, somatic symptoms (P<0.001), anxiety, interpersonal sensitivity, and hostility (P<0.05) between two intervention and control groups. There was not any significant difference in depression between intervention and control groups (P=0.11). "n"n Conclusion: Group counseling resulted in a significant reduction in severity of total PMS, somatic symptoms, anxiety, interpersonal sensitivity and hostility in intervention group compared to the control group. There was no statistically significant difference in depression between two groups."n"n  "n"n Key words: counseling, menstruation, symptoms